TRADISI METIGTIG DI DESA BEBANDEM DALAM PENCIPTAAN KARYA SENI LUKIS - Setiawan, I Komang Fergi; Yudha, I Made Bendi; Karja, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2021)
The Metigtig tradition is one of the cultural traditions associated with the nangluk mrana ritual, namely the yadnya / offering ceremony which is carried out as a form of praise and requests to Ida Sang Hyang Widhi, God Almighty. Offerings or rituals of this kind are proposed, so that by His blessings, grace and through His power could neutralize or control all forms of negative disturbances by insects or pests, as well as supernatural forces, which have a detrimental impact, especially when disease outbreaks/pandemics in plants, animals and humans. Before the implementation of the Metigtig Tradition culture, first it begins with a prayer, namely submission of oneself through the offering of true devotion to ask for salvation so that the implementation could run according to common expectations. After the prayer is carried out, it is continued with the Matumblu ceremony at Pasuwikan Temple or commonly called Usaba Sumbu, which is a ketupat that is hung using 66 (sixty six) pieces of bamboo, then tumblu (pushed using jempana) until the hanging ketupat falls.